A novel homozygous TMEM70 mutation results in congenital cataract and neonatal mitochondrial encephalo-cardiomyopathy - BEREKET, ABDULLAH; MEMİŞOĞLU, ASLI; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP (ELSEVIER SCIENCE BV, 2013)
Mutations in the TMEM70 gene are the most common cause of nuclear encoded ATP synthase deficiency resulting in a syndrome characterized by neonatal lactic acidosis, cardiomyopathy, and encephalomyopathy. Here we report on the first Turkish patient who presented after birth with lactic acidemia, severe hpotonia, hypertrophic cardiomyopathy and bilateral congenital cataract. TMEM70 genetic analysis revealed the causative homozygous c.535C>T novel mutation that result in substitution of a highly conserved tyrosine into histidine at position 179. In this report we focused on a detailed description of the clinical features of this syndrome with special emphasis on the typical facial dysmorphic features. Our report underscores TMEM70 deficiency as a pan-ethnic well defined phenotype. In cases with high suspicion sequencing of TMEM70 should be performed even before the traditional invasive muscle biopsy to confirm the diagnosis. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: TMEM70; Congenital cataract; Hypertrophic cardiomyopathy; Lactic acidosis; ATP SYNTHASE DEFICIENCY; 3-METHYLGLUTACONIC ACIDURIA; NUCLEAR-ORIGIN; DEFECTS; ONSET; GENE